Development of an Engine Performance Test Rig for a 1,497 cc Nissan GA15DE Engine Using a Friction-Type Dynamometer - เชียงคํา, สมบัติ; ตะพาบน้ำ, กรยุทธ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research presents the construction of an engine performance testing setup for evaluating the performance of a 1,497 cc Nissan GA15DE engine equipped with an automatic transmission. The tests were conducted in reverse gear to determine engine torque and brake power. The experimental results obtained using a friction-type dynamometer indicate that the engine produced a maximum torque of 42.91 N·m at 3,700 rpm and a maximum brake power of 10.106 kW at 5,200 rpm.